2017
DOI: 10.1016/j.eja.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Agriculture practices reduce the global warming potential of rainfed low N input semi-arid agriculture

Abstract: Conservation tillage and crop rotations improve soil quality. However, the impact of these practices on greenhouse gas (GHG) emissions and crop yields is not well defined, particularly in dry climates. A rainfed 2-year field-experiment was conducted to evaluate the effect of three long-term (17-18 years) tillage systems (Conventional Tillage (CT), Minimum Tillage (MT) and No Tillage (NT)) and two cropping systems (rotational wheat (Triticum aestivum L.) preceded by fallow, and wheat in monoculture), on nitrous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 58 publications
1
21
0
1
Order By: Relevance
“…Carbon dioxide (CO 2 ), methane (CH 4 ) and nitrous oxide (N 2 O) are major GHGs emitted by agricultural activities (Tellez-Rio et al 2017). In year 2005, it was estimated that globally agriculture accounted to 50 and 60% of total anthropogenic CH 4 and N 2 O emissions, respectively (Liu et al 2015).…”
Section: Agriculture and Climate Change: A Two-way Relationshipmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ), methane (CH 4 ) and nitrous oxide (N 2 O) are major GHGs emitted by agricultural activities (Tellez-Rio et al 2017). In year 2005, it was estimated that globally agriculture accounted to 50 and 60% of total anthropogenic CH 4 and N 2 O emissions, respectively (Liu et al 2015).…”
Section: Agriculture and Climate Change: A Two-way Relationshipmentioning
confidence: 99%
“…Sainju (2015) and Sainju et al (2014) found continuously cropped no-tillage systems including barley (Hordeum vulgaris L.) and pea (Pisum sativum L.) mitigated GWP compared to tilled systems including chemical fallow, though evaluated treatments were net GHG sources when emission calculations were based on changes in SOC stocks. Positive net GWP for semiarid cropping systems have also been found outside the northern Great Plains of North America [6,12,13], highlighting a systemic challenge in attaining beneficial climate regulation services from these agroecosystems. While additional GWP evaluations of semiarid cropping systems are sorely needed, novel design features of this important agroecosystem may need to be considered if meaningful GHG mitigation benefits are to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…While climatic and edaphic influences on GWP are important, management practices employed by producers are the final determinants on GWP outcomes in semiarid cropping systems. Use of no-tillage has been found effective at reducing net GWP through accrual of SOC [11][12][13]. However, as inferred above, long-term adoption of no-tillage is critical to achieve GHG benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many countries including China will have to adopt appropriate intensive production practices to ensure the sustainability of agriculture 2 . Globally, agricultural soil is thought to be one of the major contributors to greenhouse gas (GHG) emissions, accounting for 10%-12% of total anthropogenic GHGs 3 . However, agricultural soil also sequesters 4 × 10 8 − 9 × 10 8 Mg C yr −1 4 .…”
Section: Mitigation Of Greenhouse Gas Emissions Through Optimized Irrmentioning
confidence: 99%